Cationic, amphiphilic dextran nanomicellar clusters as an excipient for dry powder inhaler formulation. (1st September 2015) - Vadakkan, Mithun Varghese; Binil Raj, S.S.; Kartha, Chandrasekharan C.; Vinod Kumar, G.S.
Graphical abstract: Abstract: Effective delivery of drugs to alveoli in a controlled manner using hydrophobic polymers as carriers has already been reported. Preclinical studies revealed that toxicity and hydrophobicity are related to each other in pulmonary delivery. Here, we are reporting a chemically modified dextran having amphiphilicity and cationicity achieved by controlled grafting of stearyl amine. Two proportions of lipopolymers were synthesized and physico-chemical characterization was carried out. In vivo evaluation of sub-acute toxicity of the synthesized lipopolymer in Sprague–Dawley rats was carried out for three months. This was followed by a histological evaluation of the sacrificed animal's lung. Further, the synthesized lipopolymer was formulated with drug (Rifampicin) loaded inhalable microparticles through spray drying. The final drug formulation was tested for toxicity and proinflammatory responses in human cell lines. Dose deposition efficiency of the formulation was determined using Anderson Cascade Impactor.